Diagnóstico do sistema de esgotamento sanitário dos 50 municípios do Oeste do Paraná e proposição de modelo de gestão - Müller, Angela Maria (2021)
Untreated and inadequately disposed domestic sewage is the source of several problems in the territories, as it is a mixture of water with solid waste that carries a large number of living organisms that are harmful to human health, in addition to causing pollution of the receiving bodies. In this context, the objective of the work was to diagnose the sanitary sewage systems of the 50 municipalities in the West Region of Paraná and to propose a new model for the management of domestic effluents based on innovative technology. For this purpose, the methodology contemplated the qualitative and quantitative characterization of the level of coverage in the service of the sanitary sewage system, details of the technical and operational aspects of the sanitary sewage systems, study of the installed capacity in view of the current demand, simulation of future scenarios of the demand in 2030, prospecting of methods, processes and technologies for collecting, transporting and treating effluents, proposing a model for managing domestic effluents and assessing aspects related to the implementation feasibility. Thus, it was identified that the West Region of Paraná is composed of 50 municipalities, in general, with less than 100 thousand inhabitants, and Sanepar is the entity present in 44% of the municipalities and 58% of the municipalities do not have treatment plants. of sewage, the main individual solution for sanitary sewage is the septic tank. The municipalities that have treatment, bet on old technologies such as the anaerobic reactor; optional pond and anaerobic filter. There is a need to implement new technology that can transform domestic sewage into a source of wealth for the local population, by overcoming barriers, in addition to consequently solving the social and environmental problems encountered.